The Toxicity of a Chemically Synthesized Peptide Derived from Non-Integrin Platelet Collagen Receptors - Thomas M. Chiang; V. Woo-Rasberry (AboutScience Srl, 2008)
A chemically synthesized peptide derived from platelet non-integrin collagen receptor has been shown to be an effective agent for inhibiting collagen-induced platelet aggregation and adhesion of washed radiolabeled platelets onto natural matrices and collagen coated microtiter plates. In order to be a therapeutic agent, we have used a cell culturing system and an animal model to test its cytotoxicities. In cell culture experiments, the peptide is not toxic to MEG-01, a megakaryoblastic cell line. Prior to performing experiments in rats, the existence of both platelet type I and type III collagen receptors and its functional roles in rat platelets had to be established. In this investigation, we report that rat platelets contain both receptors and the cHyB peptide inhibits both type I and type III collagen-induced rat platelet aggregation. In addition, analysis of the rat sera collected at various time intervals following an injection of cHyB into the rat-tail vein, did not show an increase in the activity of key enzymes which indicate tissue and/or organ damage. These results suggest that the cHyB peptide is safe and its development into a potential therapeutic agent for inhibiting thrombi formation is possible.